STRATEGI KEBERLANJUTAN KERIFAN LOKAL DALAM PENGELOLAAN LINGKUNGAN DI DESA RANTAU BARU KECAMATAN PANGKALAN KERINCI KABUPATEN PELALAWAN PROVINSI RIAU - Devita Agustine; Ridwan Manda Putra; Viktor Amrifo (Pelantar Press, 2023)
One of area which still maintain its local wisdom is Rantau Baru Village, Pangkalan Kerinci District. However there is still one problem here. One of the problems is the public and the private sector still violate the rules that have been set. The purpose of this research is to analyze and describe the practice of local wisdom, find out the factors that influence the strategy of maintaining local wisdom also to analyze and describe the strategy of local wisdom. The approach used in this study is a qualitative approach. To analyze the Strategy for Maintaining the Local Wisdom of the New Rantau Village, the writer uses a SWOT analysis. The results of the research that the author found in the field are as follows: The forms of local wisdom that exist in the Rantau Baru village are the tradition of auctioning river banks and guarding sialang trees. Factors affecting the fading of the value of local wisdom are due to the low compliance of the community with the regulations made by the ninik mamak and the village government. The right strategy to maintain the local wisdom of Rantau villages is a diversification strategy. The focus of the strategy applied is the S-T strategy (a strategy that uses strength to overcome threats). a) Providing a public space for information forums regarding the importance of protecting the nature of Rantau Baru Village. b) Conduct routine counseling related to rivulet rents so that non-tenants are not exploited. c) Conduct socialization and special training for the development of tourism villages in new overseas villages